Nonna Maria and the case of the lost treasure : a novel - Carcaterra, Lorenzo (Bantam Books, 2024)
"As Nonna Maria's longtime friend and sometimes colleague, Captain Murino of the Ischian caribineri, never wanted to see harm brought to the doorstep of everyone's favorite espresso-brewing, counseling-giving amateur sleuth. But when you live a long life, you're bound to make a few enemies. And when those enemies come calling, you have to rely on friends. Faced with an assassin seeking revenge for a decades-old grudge, Captain Murino has no choice but to turn to Maria, who will have to use all her neighborly resources, clever faculties, and lifelong friends to save him from his perilous predicament. On the other side of the island, another mystery begins to unfold from the deathbed of another of Maria's old friends, a fruit peddler with a simple life, a man of modest means. Alone with his granddaughter, the man hands her a yellowed letter and tells her of a treasure to be found in one of Ischia's secret caverns, known as the Magician's Cave. There are traps and pits. There will be others with sinister motives who will do all they can in their malicious power to make the unspoken treasure their own. But this letter is a guide, a secret-the only gift he has to give. When the granddaughter needs help cracking the code, she turns to her grandfather's trusted friend, Nonna Maria. From battling foes in medieval castles to exploring the notorious caverns where smugglers hid their goods, Nonna Maria and her friends--some old, some new--embark on their most swashbuckling adventure yet."--